Visualization and Mapping of Research Topics Transportation Model Sustainable Movement for Livestock Folding Container Ship as Sea Toll Supports - Sutini Sutini; Mudjiastuti Handajani; Ismiyati Ismiyati (The Indonesian Journal of Planning and Development, 2024)
A study analyzed research on transportation models for livestock folding containers in relation to sea toll support, utilizing Crossref data and the Publish or Perish 8 software. Searches with keywords "livestock folding container" and "sea toll" from 2014 to 2023 yielded 1,000 publications across 18 document types. The data was categorized and analyzed in Microsoft Excel, with visualization conducted using VOSviewer. Results indicated a steady increase in research topics related to livestock folding containers and sea tolls since 2018. David C. Barret emerged as the most prolific author with 45 publications, while Stephen C. Bishop received the highest citations, totaling 124. The United Kingdom was identified as the leading country in this research area. Key institutions contributing significantly included the Central University of Tamil Nadu, Los Alamos National Lab, and the Scottish Center for Production Animal Health. Consistent research themes since 2018 included container, cargo, livestock, toll, Northern Sea Route, ship, vessel, transportation, sea transport, and container transportation. This study highlights the growing interest in optimizing livestock transport through innovative container designs and efficient sea toll strategies.